(untitled) (Research, Society and Development, 2024)
In this study, the effect of treatment with anethole (AN) and the combination anethole+itraconazole (AN+IT) compared to IT, on infectious arthritis induced by Paracoccidiodes brasiliensis, was evaluated. The animals were treated for 14 days at doses of anethole (AN - 62.5, 125 and 250 mg/kg), itraconazole (IT - 12.5, 25 and 50 mg/kg) and the combination of anethole+itraconazole (AN+ IT - 62.5 and 12.5 mg/kg). The parameters evaluated were: the development of knee edema, the number of leukocytes recruited into the joint cavity, the body weight of the animals, the walking capacity, the plasmatic concentration of nitric oxide, the concentration of TNF in the knee joint exudate, the production of anti-Pb antibodies and the activity of plasma transaminases (AST and ALT). Histological changes in the right knee joint of the hind paw were evaluated using Hematoxylin-eosin and Grocott staining. The results showed that treatment with monotherapies and combinations reduced knee joint edema, the number of leukocytes recruited into the synovial cavity and improved the animals’ gait. The concentration of plasma NO, tissue TNF and anti-Pb were reduced by treatment with IT at all doses tested and with the AN+IT combination. Treatment with AN only reduced the plasma concentration of NO and tissue TNF at a high dose. Altogether, the data showed that treatments with IT monotherapy and the combination of AN + IT showed a similar inhibitory effect on the development of arthritis.